The Effect of Mastery of Study Material Expertise on Readiness to Become a Teacher - Yuliyanto, Riyan; Rahmanto, Andi Adam; Ramadhan, Gilang (Lentera: Jurnal Ilmiah Kependidikan, 2023)
This study aims to determine the effect of mastery of material expertise in the field of study on readiness to become a teacher in students majoring. The method in this study uses descriptive verification. The population in this study were students majoring in social science education class 2018-2021 Faculty of Teacher Training and Education Lampung University. The sampling technique is probability sampling using stratified random sampling. Collecting data using a questionnaire. Hypothesis testing was carried out by t and F tests and processed by the SPSS program. The results of the analysis showed that there was an effect of 17.3%. If the mastery of the subject matter expertise increases, it can increase the readiness to become a prospective teacher.